Kebijakan Kriminal Terhadap Pinjaman Online Ilegal dalam Perspektif UU No. 8 Tahun 1999 Tentang Perlindungan Konsumen di Kecamatan Pandaan – Kabupaten Pasuruan - Dian, Dian; Darwis, Nurlely; Sudarto, Sudarto (Neolectura, 2024)
The phenomenon of globalization has a very broad impact on the lives of individuals, communities and countries. The impact covers various aspects such as ideology, politics, economics, socio-culture, and defence and security. Globalization can be interpreted as a process of interaction, dependency, interconnectedness, and mutual influence between individuals, groups, and countries. In the context of globalization, the life experience, ideas, and information has become a standard that applies throughout the world. This is due to increasingly sophisticated technological advances, from communication to transportation. Therefore, globalization has changed the face of the modern world and influenced the way humans live and interact. One of the influences of the global era that is of concern to the author is the problem of online loans which feels has really disrupted people's lives in society and the facts show that there have been so many victims as a result of this system. Online loans are money lending facilities by financial service providers that operate online. Because the system is virtual, online loans do not require collateral. Online loans are an innovation in the field of financial technology that makes it easier for people to borrow money. Firmly, online loans is a money loan facilitated by a financial service provider that is integrated with information technology, starting from the application process, approval to disbursement of funds carried out online or via SMS or telephone confirmation. Therefore, what online loans needs to be aware of are; 1) Loans without license. Online loans that are unregulated or do not have a license from a valid financial authority may be considered illegal; 2) Loans with high interest rates; 3) Aggressive or unfair billing; 4) Concealment of important information; 5) Identity falsification or fraud. This research was conducted in Pandaan District, Pasuruan Regency, East Java. The research method used is normative juridical using secondary data generally from the library, along with case examples, supported by empirical research based on direct experience, experiments, and observations of realities that can be observed concretely.